Pesos que gané con mi inteligencia. Doña maría del Campo Lantadilla, una adelantada (Santiago, siglo XVII) - Chiu Stange, María Luisa (Revista de Historia Social y de las Mentalidades, 2011)
This article recounts the biography of a widow, res ident of Santiago, with family ties to wealthy merchants and public officials linked to th e economic sector. Within this realm, specific references are made to the administ ration of a family farm and the production and commercialization of wine.
Keywords: Women’s history; winemaking; colonial economic history